Comparison of cytological 'jet-wash' specimens and histology in endometrial carcinoma. Issue 7 (July 1980) - Segadal, E; Iversen, O E; Ulstein, M
Abstract : Jet-washing of the uterine cavity for cytological examination has been performed in 200 patients. The results were compared with the histological diagnoses obtained by curettage. In 24 patients with endometrial carcinoma, both methods showed one specimen to be 'not adequate' while the other showed malignancy. A combination of jet-wash and curettage gave a diagnosis in 96% of patients while curettage alone gave a diagnosis in 82%, and cytology alone in 90%. The method is simple and may be of special value in postmenopausal patients.